Transcatheter aortic valve replacement in bicuspid valves: The synergistic effects of eccentric and incomplete stent deployment. (September 2021) - Qiu, Dong; Barakat, Mohammed; Hopkins, Brenna; Ravaghi, Saba; Azadani, Ali N.
Abstract: Bicuspid aortic valve is a congenital cardiac anomaly and common etiology of aortic stenosis. Given the positive outcomes of transcatheter aortic valve replacement (TAVR) in low-risk patients, TAVR will become more prevalent in the future in the treatment of severe bicuspid valve stenosis. However, asymmetrical bicuspid valve anatomy and calcification can prevent the circular and complete expansion of transcatheter aortic valves (TAVs). In previous studies, examining the impact of elliptical TAV deployment on leaflet stress distribution, asymmetric expansion of balloon-expandable intra-annular devices was studied up to an ellipticity index (long/short TAV diameter) of 1.4. However, such a high degree of eccentricity has not been observed in clinical studies with balloon-expandable devices. High degrees of stent eccentricity have been observed in self-expanding TAVs, such as CoreValve. However, CoreValve is a supra-annular device, and it was not clear if eccentric and incomplete stent deployment at the annulus would alter leaflet stress and strain distributions. This study aimed to assess the effects of eccentric and incomplete stent deployment of CoreValves in bicuspid aortic valves and compare the results to that of SAPIEN 3. Leaflet stress distribution and leaflet kinematics of 26-mm CoreValve and 26-mm SAPIEN 3 devices in bicuspid valves were obtained in a range that was observed in previous clinical studies. The results indicated that elliptical and incomplete stent deployment of TAVs increase leaflet stress and impair leaflet kinematics. The changes were more pronounced in CoreValve than SAPIEN 3. Increased leaflet stress can reduce long-term valve durability, and impaired leaflet kinematics can potentially increase blood stasis on the TAV leaflets. The study provides complementary insights into the mechanics of TAVs in bicuspid aortic valves. Graphical abstract: Image 1 Highlights: Elliptical and incomplete frame deployment of TAVs increase leaflet stress. TAV elliptical and incomplete stent deployment impair leaflet kinematics. The synergistic effects were more marked in CoreValve than SAPIEN 3. Increased leaflet stress can potentially reduce long-term valve durability. Impaired leaflet kinematics can potentially increase blood stasis on the TAV leaflets.